Performance comparison of antenna de-pointing estimation methods for SOTM terminal testing - Alazab, Mostafa; Del Galdo, Giovanni; Felber, Wolfgang; Raschke, Florian; Siegert, Gregor; Landmann, Markus (31st AIAA International Communications Satellite Systems Conference, ICSSC 2013, 2013)
Mobile satellite communication systems also referred to as SatCom-On-The-Move (SOTM) systems provide mobile users with communication services in a variety of environments, especially those completely lacking any fixed communications infrastructure such as maritime and aeronautical environments. SOTM systems find place in many market applications providing different types of services e.g. entertainment, rescue and military services. Antenna de-pointing and impairments of the Land Mobile Satellite (LMS) channel lead to degradation in the quality of the communication activity. Antenna de-pointing may lead to harmful interference to adjacent satellites. Regulatory authorities define limits for antenna de-pointing and for the Power Spectral Density (PSD) transmitted from the antenna. As an integral part of the development of SOTM systems, a demonstration of the system performance in terms of tracking capabilities is carried out. Such tests and demonstrations are usually performed in a field test where two or more operational satellites are involved. This contribution proposes a test method which avoids the employment of operational satellites and offers a reliable and repeatable environment for measuring the overall SOTM system performance. In particular, antenna pointing errors can be estimated with a high degree of precision. The pointing estimation accuracy performance of the proposed method is compared to the performance of the field test methods.
CRIS-Team Scopus Importer:2025-11-10